Sosialisasi Dan Pelatihan Sistem Informasi Potensi Desa Sebagai Upaya Peningkatan Ekonomi Kerakyatan Pada Desa Deme II - Moh. Ramdhan Arif Kaluku; Muchlis Polin (Univeristas Negeri Gorontalo, 2019)
The guidance on the need for information and the use of computers has increasingly led to the formation of a computer network capable of serving various needs, including the need for Information Systems in the village. This service is carried out to be able to support economic improvement in the village through technology facilities and information on the village potential. With the existence of this village potential information system, various village parties and village communities can develop potential sectors in the village, be it the tourism sector, agricultural sector, etc., which can be recognized by many people so that it has a positive impact on economic growth in the village. With the aim of increasing the capacity of the leadership of the village government apparatus in an effort to increase the people's economy. The method used in the implementation of socialization activities and training of village potential information systems as an effort to increase the people's economy in Deme II Village.